HOW TO SOLVE   3X= -5  THEN X= with all work shown plez,...

Expert Answers
booksnmore eNotes educator| Certified Educator

The first response is correct, but I thought I'd add a little bit about how I think about it just in case it's helpful.

Whenever I'm doing an algebra problem like this, where

x = something

the first thing I think about is "how can I separate x from the other numbers?" In this case in order to isolate "x" I have to figure out how to move the 3 to the other side.

Next to the x, 3 is a whole number or 3/1. But when I move it to the other side I have to change it. Like the original poster, I could call it 1/3 or I could say that it becomes the denominator (bottom number) of whatever whole number is already on that side. So it becomes:

1/3 of -5


1/3 x -5



Sometimes I think about it in terms of "if I multiply the number on one side, then when I move it to the other side, I must divide." (inverse operation)  Or, "whatever I do to one side, I must do to the other."

For example, if you had 1/5x = 2, you would multiple both sides by 5 in order to isolate the x.

I hope that's helpful. That's how I think of it.


malkaam | Student

3x = -5  THEN x = ?

In order to solve this we need to isolate x, 

3x = -5  

3x/3 = -5/3              (divide both sides by 3)

x = -5/3 Answer

To verify it you can input the value of x in the equation,

3x = -5

3(-5/3) = -5

-5 = -5

LHS=RHS Proved.

xoimyours | Student

Lol, apparently you are not in 10th grade. I did this in 7th. Easy work so here we go :) You have to isolate the variable X , so you need to divide -5 by 3. that would be -1.66 repeating, rounding to -2.


So X= -1.66 OR X= -2 if you ROUND.


Hope this helps. :)

neela | Student

To find x from 3x =-5 .Three times a number  is -5. Therefore, the number has to be one third of -5 or -5/3.

Solving an equation means to find the value of x. In agebra we solve an equation by simple operations on an equation. By simple operations, we mean, we can add subtract multiply or divide an  both sides of an equation  by the same number, the result is an equivalent equation only. So,

3x = -5.

Divide both sides by 3.

3x/3 = -5/3.

Simplify and we get:

3 = -5/3.